2020
DOI: 10.1177/0013124520931453
|View full text |Cite
|
Sign up to set email alerts
|

School Climate as a Link Between High School Black Males’ Math Identity and Outcomes

Abstract: The association between students’ academic identity and their academic outcomes has been well-established. The importance of a positive school climate has also been widely documented. However, Black males experience factors that uniquely and collectively comprise their school climate. As such, the purpose of this study was to test the extent to which school climate mediated the relationships between math academic identity and math outcomes of Black males. Bootstrapping mediation analyses were conducted in a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Cocorada et al 2017, measuring student academic achievement with 7 indicators into 3 categories, namely student and teacher relationships, principal participation, student interaction, school satisfaction, school achievement motivation, relationships between teachers, and safety of citizens at school (32). Negative school climate can be measured using 9 indicators, namely student tardiness, student absence, dropout students, student concern, parental participation, minimal teaching materials, insufficient teacher resources, student readiness to learn, student health conditions (33). Indicators in measuring school climate which are predicted to affect student academic achievement have been suggested by several researchers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cocorada et al 2017, measuring student academic achievement with 7 indicators into 3 categories, namely student and teacher relationships, principal participation, student interaction, school satisfaction, school achievement motivation, relationships between teachers, and safety of citizens at school (32). Negative school climate can be measured using 9 indicators, namely student tardiness, student absence, dropout students, student concern, parental participation, minimal teaching materials, insufficient teacher resources, student readiness to learn, student health conditions (33). Indicators in measuring school climate which are predicted to affect student academic achievement have been suggested by several researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Students who often arrive late, skip school, drop out of school, student apathy, lack of parental involvement, and lack of materials and resources. teachers, students not ready to learn, and students' poor health (33). A poor school climate increases the risk of student absence and impacts student achievement and risk of dropping out (34).…”
Section: Resultsmentioning
confidence: 99%
“…In another American study using data from 6,670 fifth-graders, Richard (2021) found that a positive school climate had a significant relationship with English Language Arts achievement. Another American study (Jackson et al, 2021), who used bootstrapping mediation analyses on 1,106 eleventh-grade learners, found that school climate partially explained the relationship between math identity and learner performance. Berkowitz (2021) used a multi-level model on data from 53,801 Israeli fifth-and eighth-graders, and also found school p-ISSN: 2184-044X e-ISSN: 2184-1489 ISBN: 978-989-53614-5-8 © 2022 climate to be a significant predictor of learner achievement.…”
Section: Introductionmentioning
confidence: 99%
“…School climate has become a staple of organisational-educational research and is considered here in relation to learner academic achievement. Many researchers have found school climate to be a predictor of learner achievement (Belton, 2021;Berkowitz, 2021;Jackson et al, 2021;Richard, 2021;Zysberg & Schwabsky, 2021). Belton (2021) conducted a study in Virginia, USA, using Grade 5 data from 97 schools, and found a strong correlation between school climate and learner achievement.…”
Section: Introductionmentioning
confidence: 99%
“…In another American study using data from 6,670 fifth-graders, Richard (2021) found that a positive school climate had a significant relationship with English Language Arts achievement. Another American study (Jackson et al, 2021), who used bootstrapping mediation analyses on 1,106 eleventh-grade learners, found that school climate partially explained the relationship between math identity and learner performance. Berkowitz (2021) used a multi-level model on data from 53,801 Israeli fifth-and eighth-graders, and also found school p-ISSN: 2184-044X e-ISSN: 2184-1489 ISBN: 978-989-53614-5-8 © 2022 https://doi.org/10.36315/2022v2end042 climate to be a significant predictor of learner achievement.…”
Section: Introductionmentioning
confidence: 99%